Using RAP Strategy to Teach Reading Comprehension in EFL Class - I Kadek Agus Sudarmawan (Indonesian Journal Of Educational Research and Review, 2021)
The reading ability of students in Indonesia is still low. The lack of students' reading comprehension is generally caused by ineffective strategies used by teachers in teaching reading. Students only do silent reading and are asked to answer questions from the text. This study aims to analyze the use of the RAP strategy to teach reading comprehension in EFL classes. This type of research is qualitative. This research is designed in the form of a literature study or literature study. Sources of data are taken from electronic books (e-books), research articles, and other relevant sources. The collected data is then analyzed through qualitative data analysis. Data analysis activities are carried out interactively, and the fourth stage is data collection, data reduction, data presentation, and inference/verification. The results of the study are that RAP strategies can help students to improve memory about the main ideas and details of specific texts, interactive reading strategies that offer many benefits for students in reading activities can help students in understanding texts as well as their reading comprehension, offering students opportunities to practice content, and can be done quickly by the teacher in the reading class. It can be concluded that the RAP strategy is the right strategy that teachers can use to teach reading in the classroom.